Protocol of a prospective multicenter study on comorbidity impact on multiple sclerosis and antibody-mediated diseases of the central nervous system (COMMIT) - Samadzadeh, Sara; Adnan, Rafl; Berglova, Paulina; Barzegar, Mahdi; Debrabant, Birgit; Roikjaer, Stine Gundtoft; Levy, Michael; Petzold, Axel; Palace, Jacqueline; Flanagan, Eoin P.; Mariotto, Sara; Skou, Soeren T.; et al. (Frontiers in Immunology, 2024)
Comorbidities in patients with multiple sclerosis (MS) and antibody-mediated diseases of the central nervous system (CNS) including neuromyelitis optica spectrum disorder (NMOSD), and myelin oligodendrocyte glycoprotein (MOG)-antibody-associated disease (MOGAD) are common and may influence the course of their neurological disease. Comorbidity may contribute to neuronal injury and therefore limit recovery from attacks, accelerate disease progression, and increase disability. This study aims to explore the impact of comorbidity, particularly vascular comorbidity, and related risk factors on clinical and paraclinical parameters of MS, NMOSD and MOGAD. We propose COMMIT, a prospective multicenter study with longitudinal follow-up of patients with MS, NMOSD, and MOGAD, with or without comorbidities, as well as healthy subjects as controls. Subjects will be stratified by age, sex and ethnicity. In consecutive samples we will analyze levels of inflammation and neurodegeneration markers in both fluid and cellular compartments of the peripheral blood and cerebrospinal fluid (CSF) using multiple state-of-the-art technologies, including untargeted proteomics and targeted ultrasensitive ELISA assays and quantitative reverse transcription polymerase chain reaction (RT-qPCR) as well as high-dimensional single-cell technologies i.e., mass cytometry and single-cell RNA sequencing. Algorithm-based data analyses will be used to unravel the relationship between these markers, optical coherence tomography (OCT) and magnetic resonance imaging (MRI), and clinical outcomes including frequency and severity of relapses, long-term disability, and quality of life. The goal is to evaluate the impact of comorbidities on MS, NMOSD, and MOGAD which may lead to development of treatment approaches to improve outcomes of inflammatory demyelinating diseases of the CNS.